Analisis Manajemen dan Solusi Inovatif untuk Meningkatkan Kualitas Layanan BK - Rober Sandra; Neviyarni S; Yarmis Syukur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This literature-based research underscores the crucial role of competent guidance and counseling (GC) management in achieving efficient and effective service delivery. Essential components of this management include planning, organizing, implementing, monitoring, and evaluating activities, while factors such as work distribution, order, discipline, and unified leadership serve as determining elements of success. The involvement of various school personnel is necessary in delivering GC services, considering the resources available.To enhance service quality, the study introduces innovative strategies to address challenges and ideas related to the management of guidance and counseling services in schools. Sufficient infrastructure is required to support GC programs, which should be developed according to student needs and aligned with the curriculum. Accountability and supervision play a vital role in ensuring desired outcomes. Ultimately, effective guidance and counseling not only foster studentsâ€™ independence and character development but also strengthen public confidence in the schoolâ€™s capacity to provide these services. Â